Comparison of modern retail and traditional retail reviewed from the perspective of consumers in urban and rural areas in pinrang regency - Madrianah, Madrianah; Alimuddin, Firman; Fadilah, Nurul; Sudirman, Sudirman (Jurnal Mantik, 2024)
The competition between modern and traditional retail today does not only talk about price but the competition of all aspects found in stores. The presence of modern retail businesses has changed people's behavior patterns and shopping perceptions in shopping at retail stores. The presence of modern retail has an impact on decreasing the income of traditional retail business actors. To respond to this phenomenon, it is necessary to strengthen innovation and competitiveness from traditional retail business actors. This research aims to compare the public's perception of modern retail and traditional retail in Pinrang Regency, with the focus of this research being 7 aspects in the marketing mix including Product, Price, Promotion, Place, People, Process, and Physical Evidence. The subjects of this study are people in urban and rural areas who have shopped at both types of retail. The method of data collection is through a survey with a Likert scale. The results of data analysis conducted using SPSS show that there is a significant difference in public perception of the two types of retail entities, where modern retail is superior in terms of product, price, promotion, place, people, and physical evidence in both urban and rural area public perceptions. In terms of process variables, people in urban areas prefer modern retail, while in terms of people in rural areas, they prefer traditional retail. This research is expected to contribute to the development of retail modern and retail traditional in the future